Heart rate variability in professional and semiprofessional soccer: a scoping review - Mirto, M.; Filipas, L.; Altini, M.; Codella, R.; Meloni, A. (Scandinavian Journal of Medicine & Science in Sports, 2024)
In modern soccer, fitness and fatigue monitoring tools tend to be focused on noninvasive, time-efficient and player-friendly measures. Heart rate variability (HRV) has been suggested as an effective method for monitoring training response and readiness to perform. However, there is still a lack of consensus on HRV monitoring when it comes to soccer. Thus, this scoping review aims to map existing evidence on HRV in professional and semiprofessional soccer settings, and to identify knowledge gaps to inform future research directions. A search of databases (PubMed, Scopus, Web of Science, Google Scholar) according to the PRISMA-ScR statement was employed. Studies were screened for eligibility on inclusion criteria: (1) HRV was among the topics discussed in the article; (2) adult professional or semiprofessional soccer players were involved in the study; (3) both male and female participants; (4) no geographical area exclusion; (5) articles published in English; and (6) article full text available. The search of the selected databases revealed 8456 records. The titles and abstracts of all articles were retrieved for screening of eligibility, leaving 30 articles for further consideration. Following screening against set criteria, a total of 25 studies were included in this review, the sample size of which ranged from 6 to 124 participants. The participants in the included studies were professional and semiprofessional soccer players, interviewed clubs staff, and practitioners. Along with other monitoring strategies, morning vagally mediated HRV analysis via (ultra)short-term orthostatic measurements may be an efficient way to assess training adaptations and readiness to perform in professional and semiprofessional soccer players. Further research is required to make definitive recommendations.